IMPROVING STUDENTS SPATIAL REASONING WITH COURSE LAB - Septia, Tika; Prahmana, Rully Charitas Indra; Pebrianto, Pebrianto; Wahyu, Rahma (Journal on Mathematics Education, 2018)
Geometry flat side material is crucial subject for students in senior high school. As the development of technology that increases very rapidly, it provides a chance to develop Media Interactive Learning (MPI) such as Course Lab MPI 2.4. This study was conducted to create a valid interactive multimedia teaching material, practical, and effective. Since there are correlated between spatial reasoning and student learning achievements, the influence of Course lab on the improvement of spatial reasoning is also seen. Spatial reasoning has three aspects that are mental rotation, spatial orientation, and spatial visualization. This study is a development model consisting plomp as design composed of three phases. The results obtained through this research interactive multimedia teaching material course lab based on geometry flat side were valid, practical, and effective. Students’ test scores average changed at 25 with a standard deviation of 7.07. The test results statistically demonstrated the value which means there were some differences in the average score of the initial test and final test. Course lab also led to improving students’ spatial reasoning. The multimedia developed was effective in improving both student learning achievements and spatial reasoning.